Hubungan Hospital Disaster Plan Simulation dengan Kesiapsiagaan Bencana Perawat di RSUD Prambanan Kabupaten Sleman - Qathrin Nada Nada; Ridlwan Kamaluddin Kamaluddin; Arif Imam Hidayat (Journal of Bionursing, 2020)
Background. Indonesia is well-known as a disaster-prone country. The numerous incident of disasters in Indonesia requires appropriate treatment, such as disaster preparedness efforts. Nurses play important roles during a disaster situation must be well prepared. This study was to examined the correlation between Hospital Disaster Plan Simulation and disaster preparedness level of nurses in Prambanan District Hospital Sleman. Methods. This is a quantitative research, non-experimental, descriptive correlative study with cross sectional design, 79 respondent participated in this study. The variables of nurses preparedness level were measured using the Disaster Preparedness Evaluation Tool Indonesian Version (DPET-I). Data were analyzed using a statistical descriptive and Mann Whitney with a significance level 95 %.Results. Prambanan District Hospital Nurses have a moderate level of disaster preparedness (knowledge:4,58; skills:4,33; post disaster management:4,33). Hospital Disaster Plan Simulation have a correlation with disaster preparedness level of nurses, statistical test showed significant (p < 0,05).Conclusion. Nurses need to improved disaster preparedness level by attending education, simulation like Hospital Disaster Plan Simulation, and increasing understanding of disaster management protocols in their workplace